Neurocognitive performance of patients undergoing intravenous versus oral opioid agonist treatment: a prospective multicenter study on three-month treatment effects - Chamakalayil, Sunsha; Stohler, Rudolf; Moldovanyi, Andreas; Gerber, Markus; Brand, Serge; Dürsteler, Kenneth M. (Frontiers in Psychiatry, 2024)
Introduction The first-line treatment for opioid dependence is opioid agonist treatment (OAT) with oral opioids. However, in some cases, treatment with intravenous diacetylmorphine (IV-DAM) is indicated. Research on neurocognitive impairments and treatment effects of OAT - particularly with IV-DAM - on neurocognitive functioning, is scarce. The current study is the first to investigate the neurocognitive performance of individuals on OAT with IV-DAM. Using a prospective study design with two timepoints of measurement, the first aim was to assess the nature and extent of neurocognitive functioning in individuals with opioid dependence by comparing participants’ neurocognitive performance with normative data of the general population on admission to treatment (baseline) and after an initial three-month period of OAT (study end). The second aim was to examine whether and to what extent neurocognitive performance would improve after three months on OAT. The third aim was to investigate whether, and if so, to what extent the treatment method (IV-DAM vs. oral opioids) would lead to higher neurocognitive improvements at study end. Methods Forty-seven opioid-dependent individuals (baseline; 33 individuals at study end) participated in this study (mean age: 34.3 years; 27.7% female). Participants underwent neuropsychological testing with a battery of 12 tests covering different neurocognitive domains, including attention, memory, and executive functions. Results Compared to normative data, opioid-dependent individuals showed impairments in almost every test both at baseline and at study end. At baseline, neurocognitive performance did not differ between individuals receiving IV-DAM or oral opioids for OAT. Compared to baseline, the neurocognitive performance did neither improve nor deteriorate after three months of treatment with neither IV-DAM nor oral opioids. However, a trend towards improvement was found for the memory domain. Discussion Given that neurocognitive impairments should be considered in treatment planning and therapeutic interventions. Since a reduced cognitive performance may affect both the treatment outcome and the therapeutic relationship unfavorably, specific neurocognitive training at the beginning of treatment should be considered.